The use of current sources in wire moment-method analysis and the feed-network interaction with an array. - Milligan, Tom (IEEE Antennas & propagation magazine.)
Discusses the 1.8 MHz transmitting phased array antenna of Christman (2000). The present author presents an NEC-4 analysis of the BOP (both arrays fed out of phase) and BIP (both arrays fed in phase) cases. Antenna radiation patterns are shown.